Application the Risk-Based Maintenance for Optimizing the Overall Medical Devices Safety - Khelood A. Mkalaf; Peter Gibson (Journal of Techniques)
The purpose of this study was to identify risks to patients as a result of sudden device failure during the delivery of medical treatment services. Which, can affect the reputation of hospitals following the exposure of patients' lives to various risks like death, injury, and misdiagnosis. Furthermore, a sudden failure will lead to increased economic losses as a result of increased maintenance costs.  Of (20) medical devices, (6) high-risk devices were selected, such as a ventilator, diathermy, anesthesia, BiPAP, oxygen concentrator, and electrosurgical devices. A quantitative statistical analysis based on risk-based maintenance is used to evaluate the effectiveness of the reliability of the medical device and its risks to patient lives. The results show that the reliability of the chosen medical device has declined, with higher maintenance costs due to excessive maintenance or the type of maintenance policy used. Therefore, this study provides evidence that hospitals must adopt a risk-based maintenance approach to prevent sudden failure while in service. In addition, these medical devices have various complex parts that must adopt a combination of maintenance schedules. Based on Risk-Based Maintenance's experience in improving patient safety in public hospitals in the 20 most successful OECD countries.